Miniature pediatric dental office model: A tool for assessing the behavior of school-going children in dental setting - Shivani Singh; Priya Mendiratta; Bhavna Gupta Saraf; Neha Sheoran; Disha Kapil; Ritu Singh (Wolters Kluwer Medknow Publications, 2022)
Background: Dental fear and anxiety remains the most common emotions experienced by the child who visit the pediatric dentist. The success of pedodontics is determined by the odontologist's capability to gain the confidence and maintain the cooperation of the child. Objective/Aim: The aim of the study was to assess the behavior and anxiety levels of school-going children in a dental setting using a Miniature Pediatric Dental Office Model during the first dental visit of the child. Study Design: This cross-sectional research was carried out in a dental institute in the department of pediatrics and preventive dentistry. The study protocol was explained to the parents of 3-9-year-old children. Demographics were elicited from the parents and their correlation with the placement of the doll in the pediatric dental office model and a modified Frankl's behavior rating scale was used to assess the child's behavior. Results: Of 84 participants, 47 children were under the age of 6 years and 37 children were ≥6 years of age. In the doll placement test, the majority (36.9%) of the children preferred pattern 2 (the child is on the chair, the dentist is inside the operatory, the mother is inside the operatory, and the father is outside the operatory) in the doll placement test, and the least (8.3%) preferred pattern 1 (the child is on the chair, the dentist is inside the operatory, the father is inside the operatory, the mother is outside the operatory). Thirty-four percent children up to the age of 6 years exhibited a mix of negative-positive behavior, and 43.2% of children aged 6 years showed a positive behavior according to the modified Frankl's rating scale. Conclusion: The doll placement test using a miniature pediatric office aided us in determining the child's anxiety level during their first dental visit. To achieve emotional support and avoid the impact of traumatic separation, especially in younger children, our study showed that mothers should be present in the dental office to remove behavior-related problems.